2024
DOI: 10.1038/s41557-024-01457-5
|View full text |Cite
|
Sign up to set email alerts
|

A charge-neutral organic cage selectively binds strongly hydrated sulfate anions in water

Liuyang Jing,
Evelyne Deplazes,
Jack K. Clegg
et al.

Abstract: Binding hydrophilic anions such as sulfate in water is a significant academic challenge, in particular for neutral receptors. To achieve this, typically a large molecular receptor is designed that wraps around a bound anion in a hydrophobic microenvironment. Such receptors require multi-step synthesis and often display selectivity towards hydrophobic anions such as iodide. We here report the one-pot synthesis of a [2.2.2]urea cryptand (cage) and its ability to bind sulfate in water with sub-millimolar affinity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 54 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Notably, the binding constants of L 1 to the studied anions in pure DMSO- d 6 were either numerically similar to or smaller than those of L 1 to CA4P in DMSO- d 6 /H 2 O (90%/10%, v / v ) mixed solvents. Considering the substantial decrease in binding constants observed upon water addition, as documented previously [ 40 ], we inferred that the binding affinities of L 1 to common anions are notably lower than those of CA4P. This hypothesis was reinforced by the competitive titration in DMSO- d 6 .…”
Section: Resultssupporting
confidence: 77%
“…Notably, the binding constants of L 1 to the studied anions in pure DMSO- d 6 were either numerically similar to or smaller than those of L 1 to CA4P in DMSO- d 6 /H 2 O (90%/10%, v / v ) mixed solvents. Considering the substantial decrease in binding constants observed upon water addition, as documented previously [ 40 ], we inferred that the binding affinities of L 1 to common anions are notably lower than those of CA4P. This hypothesis was reinforced by the competitive titration in DMSO- d 6 .…”
Section: Resultssupporting
confidence: 77%
“…The molecular design approach for developing sulfate selective receptors in water is dictated by a few crucial parameters, as identified in the literature on sulfate recognition. 31–42 Firstly, the larger size, tetrahedral shape, and charge density of sulfate dianion allow it to accept a maximum of twelve hydrogen bonds, which has been exemplified in several crystal structures of receptor–sulfate complexes and by theoretical calculations. 23–25 Thus, an ideal sulfate receptor should possess multiple convergent HBD groups for effective sulfate binding in the solution and solid states.…”
Section: Sulfate Selective Receptors In Aqueous Mediamentioning
confidence: 99%
“…Recently, Deplazes and Wu et al reported the synthesis of a [2.2.2]urea cryptand ( L 6 , Scheme 1) that selectively encapsulates sulfate in water with much higher affinities (SO 4 2− : log K ≈ 1.8) than that of selenate (SeO 4 2− : log K ≈ 0.93), hydrogenphosphate (HPO 4 2− : log K ≈ 0.72) and halides (Cl − /Br − : log K ≈ 0.59). 36 The charge-neutral cryptand was water soluble up to 15 mM and the sulfate binding affinity of the receptor could be enhanced to sub-millimolar levels by using micelles. The intrinsic sulfate binding constant of the cryptand in cetyltrimethylammonium bromide (CTAB) micelles was estimated >10 4 M −1 (log K ≈ 4).…”
Section: Sulfate Selective Receptors In Aqueous Mediamentioning
confidence: 99%
“…[5] Although a few neutral receptors have been reported to bind anions in 100 % water, only weakly hydrating anions are involved, such as Cl À , [6] I À , [7] H 2 PO 4 À [8] and SO 4 2À . [9] To the best of our knowledge, no charge-neutral anion receptor has been reported to bind the highly hydrated PO 4 3À in 100 % water up to now.…”
Section: Introductionmentioning
confidence: 98%
“…We attributed the upfield shift to the breaking of intramolecular hydrogen bonds after phosphate binding, a phenomenon commonly seen in the literature. [9] The absence of downfield shifts in H7-H10 of morpholine suggests there are no electrostatic interactions between the phosphate anion and L 1 . These results, including pKa values and 1 H NMR shifts at different pH levels, collectively demonstrate that the charge-neutral L 1 , rather than the positively charged L 1 , exerted the binding ability to PO 4 3À at pH 13.…”
mentioning
confidence: 99%